Potencial biotecnológico do Paenibacillus polymyxa RNC-D, endofítico isolado de Prunnus sp. (Cerrado), para atividade antimicrobiana e inflamação aguda - Cavicchioli, Rafael (Universidade Federal de São Carlos, 2017)
The variety of environmental factors to which Cerrado or Savanna vegetation is subjected has favored the potential for the synthesis of new compounds by the plants and also by the endophytes isolated from them, which are characterized as fungi or bacteria that host the plant tissue without establishing harm. The Cerrado is characterized as an excellent mosaic of biomes for endophytic research. Endophytes found on its environment displayed great biotechnological potential, producing new compounds with antimicrobial, enzymatic, leishmanicidal, antitumor, anti-inflammatory, analgesic, diuretic and cicatrizant activities. In this context, the present work aimed to evaluate the biotechnological potential of the Paenibacillus polymyxa strain RNC-D isolated from the plant species Prunnus sp. Concerning the antagonistic activity of phytopathogenic fungi in vitro. The results obtained were: Ceratocystis paradoxa (negative) Colletotrichum sp. (40%), Fusarium oxysporum (51.7%), Phytophthora sojae (61.3%) and Rhizopus microsporus (negative). Also as antimicrobial activity, in vitro, the Fresh crude extract produced in medium Yeast extract peptone mannitol, filtered, the obtained results were: Candida albicans (negative), Citrobacter freundii (15mm), Enterococcus faecalis (14mm), Escherichia coli (17mm ), Micrococcus luteus (15mm), Proteus sp. (Negative) Salmonella sp. (16mm), Staphylococcus aureus (15mm), Staphylococcus epidermidis (12mm), Staphylococcus saprophyticus (18mm). The search for substances and anti-inflammatory compounds is of great importance for the control of inflammation, since the nonsteroidal anti-inflammatory have severe side effects such as gastrointestinal reactions, severe dyspepsia, gastric and duodenal ulcers. Carrageenan-stimulated paw edema model (acute inflammation) was used to evaluate the extracts for their anti-inflammatory potential. Later on, the effects that contributed to the reduction and control of this process were observed, showing a positive effect in the temperature drop in the groups treated with extract, this presented effect was similar to that exhibited by the commercial treatment sighting at a possible and promising anti-inflammatory to be evaluated in other experimental models.
Biotechnological potential of Paenibacillus polymyxa RNC-D, endophytic isolated of Prunnus sp. (Savana), for antimicrobial activity and acute inflammation
Keywords: Anti-inflamatórios; Antimicrobianos; Bioatividade; Metabólitos secundários; Fitopatógenos; CIENCIAS BIOLOGICAS::IMUNOLOGIA::IMUNOLOGIA APLICADA; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA